1971
DOI: 10.1111/j.1939-0025.1971.tb01129.x
|View full text |Cite
|
Sign up to set email alerts
|

Milieu characteristics of successful psychiatric treatment programs.

Abstract: Characteristics of efficient (high turnover) and effective (low return rate) psychiatric units were examined. Nursing staff and patients tended to attribute negative characteristics to efficient units. Effective programs, on the other hand, were characterized as having motivated professional staff and active participant roles for both nursing staff and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0

Year Published

1972
1972
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(40 citation statements)
references
References 12 publications
(3 reference statements)
3
37
0
Order By: Relevance
“…In contrast to these findings, Ellsworth et al (1971), Holland (1973Holland ( , 1981, Cummings and Berger (1976), Martin and Segal (1977), Prager and Schnit (1985/86), and Whiddon and Martin (1987) have found that services are improved under conditions of decentralized decision-making in which the staff of the service is actively involved. A more recent study (Sherman, 1988) found that centralization of authority in voluntary organizations has negative effects on organizational effectiveness, and that structural decentralization enhances participation and involvement.…”
Section: Introductionmentioning
confidence: 81%
“…In contrast to these findings, Ellsworth et al (1971), Holland (1973Holland ( , 1981, Cummings and Berger (1976), Martin and Segal (1977), Prager and Schnit (1985/86), and Whiddon and Martin (1987) have found that services are improved under conditions of decentralized decision-making in which the staff of the service is actively involved. A more recent study (Sherman, 1988) found that centralization of authority in voluntary organizations has negative effects on organizational effectiveness, and that structural decentralization enhances participation and involvement.…”
Section: Introductionmentioning
confidence: 81%
“…He later modified the subscales after factor analysis to include five dimensions: Active Treatment, Socioemotional Activity, Patient Self-management, Behavior Modification, and Instrumental Activity (Jackson, 1969). Ellsworth, Maroney, Klett, Gordon, and Gunn (1971) Moos (1968) revised this questionnaire for correctional settings, naming it the Social Climate Scale (SCS), with the same dimensions. Further revisions led to the Correctional Institutions Environment Scale (CIES), with the Affiliation, Aggression, Variety, and Halo subscales eliminated (Wenk & Moos, 1972).…”
mentioning
confidence: 99%
“…The stage 1 treatment contract begins with three goals: (1) to clarify the diagnosis and learn basic information about risk factors and course; (2) to describe the chain of events leading to admission, and (3) to learn basic coping strategies for depression and anxiety. Psychoeducation addresses the first goal.…”
Section: Interpersonal Connectionsmentioning
confidence: 99%
“…Structure is central to milieu treatment [1][2][3]5,7,18,45,46,51,74,83,84 since it is the framework within which treatment occurs, and serves as the foundation for containment and coherence of treatment. The structure is also resilient: mechanisms are in place to anticipate and implement changes through a predictable process.…”
Section: Program Structurementioning
confidence: 99%